Stimuli-Responsive Polymer Systems-Recent Manufacturing Techniques and Applications - Kaynak, Akif (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Stimuli-responsive polymer systems can be defined as functional materials that show physical or chemical property changes in response to external stimuli such as temperature, radiation, chemical agents, pH, mechanical stress, and electric and magnetic fields. Recent developments in manufacturing techniques have facilitated the production of a wide range of stimuli-responsive polymer systems, such as micro- and nanoscale structures, with potential applications in soft sensors and actuators, smart textiles, soft robots, and artificial muscles. This book brings together the recent progress in manufacturing techniques, with particular emphasis on 3D and 4D printing and applications of stimuli-responsive polymer systems in biomedicine and soft robotics.